HAEMOPTYSIS AND HIDDEN THREATS: UNRAVELLING FOLLICULAR THYROID CANCER IN PREGNANCY - Bay, Shing Shen; Muhammad, Nur Farrah Anima; Abdan, Azzahrah; Yusof, Yuhanis; Muthusamy, Gunavathy; Jalal, Fadzliana Hanum (Journal of the ASEAN Federation of Endocrine Societies, 2024)
INTRODUCTION Haemoptysis in pregnancy is a rare but serious complication that demands prompt investigation and intervention. While pulmonary embolism is often considered, it is essential to explore other potential underlying pathologies such as lung cancer, bronchiectasis or infectious causes. In rare cases, metastatic differentiated thyroid cancer may present with haemoptysis as the primary symptom. CASE We describe a distinctive case involving a 30-year-old female in her 34th week of twin pregnancy. She had a history of left partial thyroidectomy four years prior for a large thyroid nodule. Histopathology showed papillary-like nuclear features in favour of adenomatous hyperplasia. Haemoptysis began at 20 weeks of pregnancy and increased significantly in amount at 34 weeks. There were no constitutional symptoms. On examination, she was not tachypnoeic, with SpO2 98% under room air, BP 133/70 mmHg and HR 108 bpm. She appeared clinically euthyroid, with unremarkable physical findings. Initial blood tests including full blood counts, renal profile and liver function tests were all within normal ranges. Thyroid function tests indicated normal TSH (3.699 m IU/L) and fT4 (13.27 pmol/L). However, D-dimer levels were elevated (3.04 mg/L). Tuberculosis screening with sputum AFB was negative. CT imaging showed multiple bilateral scattered enhancing lung nodules, predominantly in the lower lobes, with possible haemorrhagic nodules in the left lower lobe. She was scheduled for elective caesarean section at 36 weeks with combined care from the respiratory, obstetric and anaesthesia teams. CT-guided biopsy of the lung lesion at two weeks postdelivery confirmed metastatic follicular thyroid carcinoma. CONCLUSION This case highlighted the slow and insidious nature of differentiated thyroid cancer with lung metastases which unfortunately were presented during pregnancy. Thorough evaluation in pregnant patients presenting with haemoptysis are of utmost importance.